Detection of cardiac arrhythmias using RNA-MLP with PSO - Zatt, Augusto P.; Machado, Juliano C.; Balbinot, Alexandre (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS), 2025)
This work proposes and evaluates a cardiac arrhythmia classifier based on a Multilayer Perceptron (MLP) Artificial Neural Network (ANN) optimized by the Particle Swarm Optimization (PSO) algorithm. The model was trained and validated using a 10-fold cross-validation scheme, achieving remarkable performance metrics, with an average F1-score of 99.17%, precision of 99.2%, and sensitivity of 99.16%. The analysis of the learning curves, which show the training and validation loss converging in parallel, refutes the overfitting hypothesis. Although PSO is computationally more expensive than traditional gradient-based optimizers, this study demonstrates that this cost is a strategic investment. The meta-heuristic approach promotes robust convergence and the ability to escape local minima, resulting in a superior solution with a high generalization capability. The results confirm the effectiveness and robustness of the MLP-PSO combination for high-performance classification.